Protocol of a randomised controlled trial on the efficacy of medication optimisation in elderly inpatients: medication optimisation protocol efficacy for geriatric inpatients (MPEG) trial. Issue 10 (12th October 2020) - Ie, Kenya; Hirose, Masanori; Sakai, Tsubasa; Motohashi, Iori; Aihara, Mari; Otsuki, Takuya; Tsuboya, Ayako; Matsumoto, Hiroshi; Hashi, Hikari; Inoue, Eisuke; Takahashi, Masaki; Komiya, Eiko; et al.
Abstract : Introduction: Whether medication optimisation improves clinical outcomes in elderly individuals remains unclear. The current study aims to evaluate the effect of multidisciplinary team-based medication optimisation on survival, rehospitalisation and unscheduled hospital visits in elderly patients. Methods and analysis: We report the protocol of a single-centre, open-label, randomised controlled trial. The enrolled subjects will be medical inpatients, aged 65 years or older, admitted to a community hospital and receiving five or more regular medications. The participants will be randomly assigned to receive either an intervention for medication optimisation or the usual care. The intervention will consist of a multidisciplinary team-based medication review, followed by a medication optimisation proposal based on the Screening Tool of Older Persons' potentially inappropriate Prescriptions/Screening Tool to Alert doctors to the Right Treatment criteria and an implicit medication optimisation protocol. Medication optimisation summaries will be sent to primary care physicians and community pharmacists on discharge. The primary outcome will be a composite of death, unscheduled hospital visits and rehospitalisation until 48 weeks after randomisation. Secondary outcomes will include each of the primary endpoints, the number of prescribed medications, quality of life score, level of long-term care required, drug-related adverse events, death during hospitalisation and falls. Participants will be followed up for 48 weeks with bimonthly telephone interviews to assess the primary and secondary outcomes. A log-rank test stratified by randomisation factors will be used to compare the incidence of the composite endpoint. The study was initiated in 2019 and a minimum of 500 patients will be enrolled. Ethics and dissemination: The study protocol has been approved by the Institutional Ethical Committee of St. Marianna University School of Medicine (No. 4129). The results of the current study will be submitted to a peer-reviewed journal. Trial registration number: UMIN000035265